الشق الشرجي (Latakia University Journal -Medical Sciences Series, 2019)
يعتبر الشق الشرجي من أكثر الآفات الشائعة منذ القدم، إذ وضع أول وصف لها منذ حوالي قرنين من الزمن. والشق عبارة عن تمزق أو شرخ أو قرحة طولا نية تقع على المحور الطولاني لأسفل قناة الشرج تحت الخط المسنن عادة على الوجه الخلفي للشرج (90% من الحالات وسطيا ). من أهم مسبباته الإمساك المزمن والحمل والولادات والاستئصال الجائر لمخاطية الشرج والمستقيم في حالات جراحة البواسير. كما تلعب المعالجة الخاطئة للبواسير الشرجية باستعمال الماسورة الخاصة بالمراهم الشرجية الحادة المقطع والقاسية دورا في الإصابة بالشقوق الشرجية. الإناث أكثر إصابة من الذكور 1/2تقريبا، وأكثر أشكاله مشاهدة هو الشق المزمن (65% من الحالات) وحوالي ربع الحالات تكون مترافقة بأمراض شرجية أخرى خاصة البواسير، وأهم تظاهراته الألم الحاد والنزف. عولجت هذه الحالات في مشفانا جراحيا بثلاث طرق، كانت أكثرها شيوعا طريقة استئصال الشق وخزع المصرة الخلفي مع خياطة مخاطية الشرج مع الجلد لنتائجها الجيدة وقلة مضاعفاتها. Anal fissure is the most common problem in anus. It was first described two centuries ago. An anal fissure is a split in the anoderm in either the posterior or anterior midlin just distal to the dentate line. 90% of our anal fissure cases occure postriorly. The cause of the anal fissures has been postulated to be: chronic constipation, pregnancy, extensive mucosal resection during Haemorrhoidectomies. Also the incorrect treatment of piles – o.g using the special adopter for piles ointments application – can be considered a cause of anal fissure .The Ratio of females to meles is about 2/1. Chronic anal fissure is the most common from (65%of all cases). 25% are accompanied with the anal diseases such as piles. The typical manifest tires of anal fissure are extreme pain during defecation and red blood streaking the stool. These cases were treated surgically in 3 different rethodes the commonest one was the dorsal fissurectomy and postesior sphincterotomy. This method has better results and less complication.